(untitled) (KULT_online, 2010)
As a successful paradigm, network metaphors and concepts are used in both science and the humanities. The volume Netzwerke. Allgemeine Theorie oder Universalmetapher in den Wissenschaften? (Networks: General Theory or Universal Metaphor in Sciences and Humanities?) gathers papers dealing with different network concepts, promising to outline a transdisciplinary account of networks. However, it pursues a generalised approach of ‘network analysis’ across several disciplines rather than inquiring into networks as metaphor and theory – or the relationships between them.